What causes cryptogenic fibrosing alveolitis? A case-control study of environmental exposure to dust. Issue 6759 (3rd November 1990) - Scott, J; Johnston, I; Britton, J
Abstract : OBJECTIVE--To investigate the role of occupational and domestic exposure to dust in the aetiology of cryptogenic fibrosing alveolitis. DESIGN--Matched case-control study. SUBJECTS--40 Patients with cryptogenic fibrosing alveolitis and 106 community controls matched for age and sex who responded to a questionnaire. MAIN OUTCOME MEASURE--Responses to self administered questionnaire asking about lifetime exposure to dust, animals, and smoke at home and at work. RESULTS--The patients with cryptogenic fibrosing alveolitis were more likely to report occupational exposure to metal dust (matched odds ratio 10.97 (95% confidence interval 2.30 to 52.4), p less than 0.001) or wood dust (2.94 (0.87 to 9.90), p = 0.08), to have worked with cattle (10.89 (1.24 to 96.0), p = 0.01), and to have lived in a house heated by a wood fire (12.55 (1.04 to 114), p = 0.009). A history of smoking and social class based on occupation were not significantly related to disease state. CONCLUSION--Environmental exposure to dust may be an important factor in the aetiology of cryptogenic fibrosing alveolitis.